Environmental and Hunter-Gatherer Responses to the White River Ash East Volcanic Eruption in the Late Holocene Canadian Subarctic - Kristensen, Todd J.; Beaudoin, Alwynne B.; Ives, John W. (The Arctic Institute of North America, 2020)
The eastern lobe of the Alaskan White River Ash volcanic event of AD 846 – 848 blanketed portions of Yukonand Northwest Territories, Canada, in 5 to 50 cm of tephra. The eruption has been linked to concurrent changes among hunter- gatherers, including the spread of new technologies and the continent-wide migration of a group of Dene ancestors from Subarctic Canada to the United States. We use published palaeoenvironmental data (primarily pollen and charcoal profiles) as well as studies of modern ash fall ecology and human health hazards associated with eruptions to reconstruct effects of the White River Ash east event on northern hunter-gatherer subsistence. While many components of local ecosystems appear to have rebounded quickly from ash deposition, we deduce a more pronounced impact on the important game species of caribou and salmon, the seasonal migration paths of which were intersected by thick deposits of ash. A trophic model informed by palaeoenvironmental data and ethnohistoric records suggests that negative biological effects of the ash temporarily pushed hunter-gatherer populations to neighbouring and less affected kin groups for up to 100 years. This synthesis contextualisesarchaeological theories of human responses to ecological disturbance events in circumpolar landscapes. Le lobe occidental du dépôt de cendres volcaniques White River Ash, en Alaska, remontant aux années 846 – 848A.D., a recouvert certaines parties du Yukon et des Territoires du Nord-Ouest, au Canada, d’une couche de téphra de 5 à 50 cm. Cette éruption a été liée à des changements simultanés chez les chasseurs-cueilleurs, dont l’adoption de nouvelles technologies et la migration à l’échelle du continent d’un groupe d’ancêtres dénés, de la zone subarctique canadienne jusqu’aux États-Unis. Nous avons publié des données paléoenvironnementales (principalement des profils de pollen et de charbon de bois) ainsi que des études d’écologie moderne de chutes de cendres et de dangers pour la santé des êtres humains découlant d’éruptions ...